Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.
Keywords: Photo

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.
Keywords: Xray

Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐Ru(II) complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Photo

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Photo

Planar Iron Hydride Nanoclusters: Combined Spectroscopic and Theoretical Insights into Structures and Building Principles - Chakraborty, Uttam; Bügel, Patrick; Fritsch, Lorena; Weigend, Florian; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemistryOpen)
The controlled assembly of well-defined planar nanoclusters from molecular precursors is synthetically challenging and often plagued by the predominant formation of 3D-structures and nanoparticles. Herein, we report planar iron hydride nanoclusters from reactions of main group element hydrides with iron(II) bis(hexamethyldisilazide). The structures and properties of isolated Fe4, Fe6, and Fe7 nanoplatelets and calculated intermediates enable an unprecedented insight into the underlying building principle and growth mechanism of iron clusters, metal monolayers, and nanoparticles.
Keywords: General Chemistry

When Donors Turn into Acceptors: Ground and Excited State Properties of FeII Complexes with Amine-Substituted Tridentate Bis-imidazole-2-ylidene Pyridine Ligands - Vukadinovic, Yannik; Burkhardt, Lukas; Päpcke, Ayla; Miletic, Anabel; Fritsch, Lorena; Altenburger, Björn; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Stereoselective Alkyne Hydrogenation by using a Simple Iron Catalyst - Gregori, Bernhard J.; Schwarzhuber, Felix; Pöllath, Simon; Zweck, Josef; Fritsch, Lorena; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry